Ethics, values and civil society - Cohen, Stephen; Harris, Howard; Schwartz, Michael (Research in ethical issues in organizations, 2013)
This volume is a selection of papers from the 19th annual 'Australian association for professional and applied ethics' conference. Topics covered include journalism ethics, organ donation, as well as an essay drawn from Daniel Wueste's keynote address on the conditions and implications of trust for the professions. Other papers include research on the ethical perils of university researchers, a values based approach to ethical culture, the ethics of hospitality-tourism practice and pedagogy, and ethical decision making processes for research in small and medium enterprises.